The effectiveness of ICT implementation in learning process among deaf children: how they understand a story / Sri Fatiany Abdul Kader Jailani - Abdul Kader Jailani, Sri Fatiany (2007)
The attempt to produce this thesis is to clarify how effective the deaf students understand in their learning process by using Information Communication and Technology (ICT) in implementing a story. This thesis compares the effectiveness of the ICT and visual story towards deaf children at primary special schools in the state of Kuala Lumpur. A sample of 28 students was selected from 2 special schools in Kuala Lumpur from certain ages. They were instructed to sit for a test to determine their level of understanding on a story using computers. The results were based on the level of understanding of the students using computers and by sign language. This result will also determine the level of competency of the students in using ICT to help them understand and assist them in their learning process. The limitations and directions for future development and research are discussed accordingly.